2019
DOI: 10.1016/j.ypmed.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in purchases of energy-dense nutrient-poor foods in Mexico associated with the introduction of a tax in 2014

Abstract: In 2014, an 8% tax on energy-dense nutrient-poor foods was implemented in Mexico with the aim of reducing its consumption. This paper estimated changes in household purchases of taxed food. We used the latest five waves of the nationally representative Mexican Income and Expenditure Survey (2008, 2010, 2012, 2014 and 2016). The analytic sample comprises 154,777 households. We estimated changes based on a before and after comparison. Results show a reduction in purchases of taxed food of −5.4 grams/week per cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 17 publications
2
52
1
3
Order By: Relevance
“…Some countries such as Brazil [35,36] and Uruguay [37] officially incorporated UPF in their food-based dietary guidelines. In addition, some countries, such as Chile [38], implemented policies to restrict the marketing of junk food products to children, and other countries, such as Mexico [39,40] and Hungary [41], introduced fiscal measures, such as a tax on junk food. The tax in Mexico has already demonstrated a positive effect with significant declines in the purchases of several categories of UPF [39].…”
Section: Discussionmentioning
confidence: 99%
“…Some countries such as Brazil [35,36] and Uruguay [37] officially incorporated UPF in their food-based dietary guidelines. In addition, some countries, such as Chile [38], implemented policies to restrict the marketing of junk food products to children, and other countries, such as Mexico [39,40] and Hungary [41], introduced fiscal measures, such as a tax on junk food. The tax in Mexico has already demonstrated a positive effect with significant declines in the purchases of several categories of UPF [39].…”
Section: Discussionmentioning
confidence: 99%
“…The taxes had a differential effect by wealth in urban areas; households with lower wealth reduced the purchases of taxed products the most (40)(41)(42) . But the prices of taxed products did not increase substantially in rural areas, (43) and hence this policy had a lower effect in rural areas (44) . We found that the prevalence of overweight and obesity is still larger in urban areas compared with rural areas among children and adolescent women, but among adult women, there was no difference in the prevalence, or this was higher among rural areas for obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the HDNA is the first unhealthy food tax in the United States, there are examples of similar taxes (3)(4)(5)(6)(7)(8) internationally and in several large municipalities in the United States (9,10). Those taxes were typically higher than the 2% HDNA tax, and consumption and revenue decreased after enactments.…”
Section: Objectivementioning
confidence: 99%